Religious Approach Through Interpretation of the Quran in the Case of Baby Blues Syndrome; A Study of Living Qur'an - Huda, Ade Naelul; Fitriana, Muhammad Azizan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
baby blues syndromeor postpastrum blues is an emotional disorder experienced by a woman after giving birth due to emotional stress before and after childbirth. The resolution of the baby blues cases so far has used a health and psychological approach. This article attempts to offer a new approach in handling cases of baby blues syndrome, namely a religious approach through the interpretation of the verses of the Qur'an. This study aims to determine the response of the religious approach through the elaboration of the interpretation of the verses of the Qur'an in the case of the baby blues syndrome. This research is also a model for grounding the Qur'an in the context of daily life, so that the Qur'an is not only a meaningless text, but can also be applied to solve various life problems. The method used is qualitative with the Living Quran approach. The research data were analyzed using dynamic significance analysis theory. The research shows that the religious approach through the interpretation of the verses of the Qur'an on the incidence of baby blues syndrome can be well received so that it is hoped that this research can contribute to helping reduce the incidence of baby blues through a religious approach, in addition to medical and psychological methods.